ECGs by example - Jenkins, Richard Dean; Gerred, Stephen John (Elsevier/Churchill Livingstone, 2011)
This unique book shows ECGs as they really appear in everyday practice. Each of the individual traces is accompanied by a list of the main diaganostic features along with a full report of the ECG, noting any other clinical details that may be important